Astaxanthin enhances erlotinib-induced cytotoxicity by p38 MAPK mediated xeroderma pigmentosum complementation group C (XPC) down-regulation in human lung cancer cells. Issue 6 (19th September 2018) - Chen, Jyh-Cheng; Wu, Chia-Hung; Peng, Yi-Shuan; Zheng, Hao-Yu; Lin, Yuan-Cheng; Ma, Peng-Fang; Yen, Ting-Chuan; Chen, Tzu-Ying; Lin, Yun-Wei
Graphical Abstract: Abstract: Astaxanthin has been demonstrated to exhibit a wide range of beneficial effects that include anti-cancer and anti-inflammatory properties. Xeroderma pigmentosum complementation group C (XPC) protein is an important DNA damage recognition factor in nucleotide excision repair and is involved in regulating non-small cell lung cancer (NSCLC) cell proliferation and viability. Erlotinib (Tarceva R ) is a selective epidermal growth factor receptor (EGFR) tyrosine kinase inhibitor that has demonstrated clinical activity in NSCLC cells. However, whether astaxanthin and erlotinib could induce synergistic cytotoxicity in NSCLC cells through modulating XPC expression is unknown. In this study, we found that p38 MAPK activation by astaxanthin decreased XPC expression in two human lung adenocarcinoma A549 and H1975 cells. Inactivation of p38 MAPK by pharmacological inhibitor SB203580 or the specific small interfering RNA (siRNA) rescued the astaxanthin-reduced XPC mRNA and protein levels. Enforced expression of XPC cDNA or inhibiting the p38 MAPK activity reduced the cytotoxicity and cell growth inhibition of astaxanthin. In contrast, knockdown of XPC using siRNA enhanced the cytotoxic effects of astaxanthin. Moreover, astaxanthin synergistically enhanced cytotoxicity and cell growth inhibition of erlotinib in NSCLC cells, which were associated with the down-regulation of XPC expression and activation of p38 MAPK. Our findings suggested that the astaxanthin induced p38 MAPK mediated XPC down-regulation enhanced the erlotinib-induced cytotoxicity in A549 and H1975 cells.